The composition dependence of magnetic, electronic and optical properties of Mn-doped SixGe1−x nanowires. (9th June 2017) - Wei, Jianglin; Lan, Mu; Zhang, Xi; Xiang, Gang
Abstract: Mn-doped Six Ge1−x nanowires (NWs) with different Ge concentrations have been studied by first-principles calculations. It is found that the spin dependent energy bands of the NWs show rich variations both in bandgap width and type (from indirect to direct) as the Ge concentration changes. The Mn-doped Six Ge1−x NWs exhibit half-metallic characteristics for all Ge concentrations, and the ground states of the NWs are found to be ferromagnetic (FM). The net magnetization mapping and spin density of states calculations reveal that Mn 3 d electrons have a strong hybridization effect with nearest Ge 4 p electrons, which results in the Ge's nontrivial contribution to the magnetic moment of the NWs. Further magnon dispersion studies show that the magnetic order stability of the NWs is influenced by Ge concentrations. Finally, the dependence of the optical properties of the magnetic NWs on the Ge concentration is demonstrated. Our results suggest that Mn-doped Six Ge1−x NWs may be useful in spintronic and optoelectronic devices.